The association between TSH and thyroid hormones in the normal or subclinical dysfunction range with left ventricular diastolic dysfunction - Ji Eun Jun; Tae Hyuk Kim; Sun Wook Kim; Jae Hoon Chung; Jae Hyeon Kim; You-Bin Lee; Mira Kang (Scientific Reports, 2024)
Abstract Thyroid hormones modulate the cardiovascular system. However, the effects of subclinical thyroid dysfunction and euthyroidism on cardiac function remain unclear. We investigated the association between left ventricular (LV) diastolic dysfunction and subclinical thyroid dysfunction or thyroid hormones within the reference range. This cross-sectional study included 26,289 participants (22,197 euthyroid, 3,671 with subclinical hypothyroidism, and 421 with subclinical thyrotoxicosis) who underwent regular health check-ups in the Republic of Korea. Individuals with thyroid stimulating hormone (TSH) levels > 4.2 µIU/mL and normal free thyroxine (FT4, 0.78–1.85 ng/dL) and triiodothyronine (T3, 76–190 ng/dL) levels were defined as having subclinical hypothyroidism. Individuals with serum TSH levels < 0.4 µIU/mL and normal FT4 and T3 levels were defined as having subclinical thyrotoxicosis. The cardiac structure and function were evaluated using echocardiography. LV diastolic dysfunction with normal ejection fraction (EF) was defined as follows: EF of > 50% and (a) E/e’ ratio > 15, or (b) E/e’ ratio of 8–15 and left atrial volume index ≥ 34 mL/m2. Subclinical hypothyroidism was significantly associated with cardiac indices regarding LV diastolic dysfunction. The odds of having LV diastolic dysfunction was also increased in participants with subclinical hypothyroidism (adjusted odds ratio [AOR] 1.36, 95% confidence interval [CI], 1.01–1.89) compared to euthyroid participants. Subclinical thyrotoxicosis was not associated with LV diastolic dysfunction. Among the thyroid hormones, only serum T3 was significantly and inversely associated with LV diastolic dysfunction even within the normal range. Subclinical hypothyroidism was significantly associated with LV diastolic dysfunction, whereas subclinical thyrotoxicosis was not. Serum T3 is a relatively important contributor to LV diastolic dysfunction compared to TSH or FT4.